Fonsecaea pedrosoi: A rare cause of dental infection and maxillary osteomyelitis in a child with acute lymphoblastic leukemia - Tural-Kara, Tuğçe; Özdemir, Halil; İnce, Elif; İleri, Talia; Çiftçi, Ergin (The Turkish Journal of Pediatrics, 2016)
Dental lesions are commonly seen in children with malignancy. We report a child with acute lymphoblastic leukemia who had black-brown dental lesion during the febrile neutropenic episode. Histopathological examination of dental lesion showed fungal hyphae and conidia. F. pedrosoi that was isolated from the tissue culture. The patient was treated with intravenous liposomal amphotericin B therapy for 5 weeks and he was discharged on oral voriconazole. On follow-up, clinical symptoms recovered. Although F. pedrosoi may be an unusual causative agent of dental infection and maxillary osteomyelitis, it should be considered in patient with black-brown lesions which do not respond to antibacterial treatment.
Keywords: Fonsecaea pedrosoi; acute lymphoblastic leukemia; children; dental infection; osteomyelitis.